Influence of HMTA ligand in MMA AGET ATRP emulsion polymerization. Issue 38 (21st February 2020) - Awad, Mohammed; Dhib, Ramdhane; Duever, Thomas
Abstract: Interactions of hexamethylenetetramine ligand in atom transfer radical polymerization initiated by activator generated by electron transfer were studied. Polymerization of methyl methacrylate was done using two‐step experimental procedure in 2 L emulsion batch reactor at 50, 60, and 80°C. The selection of reactant ratios was quite challenging for a reactor of this size. Replicate runs were conducted for data reproducibility purpose. Gravimetry method and gel permeation chromatography were used to determine monomer conversion, Mn, and PDI of polymer samples. PMMA produced was also characterized by means of dynamic light scattering, Fourier‐transform infrared spectroscopy and nuclear Magnetic Resonance spectroscopy. Results showed high monomer conversion up to 93% and Mn ranging 243–274 kg/mol with PDI from 1.45 to 1.60. Besides, combining HMTA with sodium dodecyl sulfate, an anionic surfactant, a well‐controlled polymer with a lower Mn of 201 kg/mol and PDI of 1.56 was obtained in 3 hr reaction time. Abstract :